Obtaining consensus on core components of stuttering intervention for adults: An e-Delphi Survey with key stakeholders - Connery, Amy (My University, 2022)
Background: Evidence-based practice involves the synthesis of multiple forms of evidence to inform clinical decision-making and treatment evaluation. Practice- and patient-based evidence are two forms of evidence that are under- represented in the stuttering literature. The collection of such knowledge is essential to support the design and delivery of effective stuttering interventions for adults. Aims: To build stakeholder consensus on the core components of intervention for adults who stutter, and to establish a guiding framework for the design and development of evidence-based interventions for adults who stutter. Methods & Procedures: Adults who stutter and speech and language therapists (SLTs) with experience in providing stuttering intervention participated in the three-round e-Delphi Survey focused on: (1) identifying key stuttering inter- vention components, including principles, practices, and structural and contex- tual elements; and (2) obtaining group consensus on stuttering intervention com- ponents. Statements were categorized using the International Classification of Functioning, Disability and Health (ICF) model adapted to the study of stuttering. Outcomes & Results: A total of 48 individuals agreed to participate: 48/48 (100%) completed the Round 1 questionnaire, 40/48 (83%) responded to Round 2 and 36/40 (90%) participated in Round 3. Following content analysis of Round 1, 101 statements were developed, and consensus was achieved on 89 statements perceived as representing the core components of stuttering intervention for adults. Categorization of these statements reflected the key stuttering intervention components relating to personal reactions to stuttering, limitations in life participation and environmental factors. Conclusions & Implications: Consensus on the core components of stutter- ing intervention was reached through engagement with key stakeholders. The evidence-based framework presented highlights the range of key intervention components a clinician should consider when designing interventions for adults who stutter.
PUBLISHED
Keywords: adults, consensus, e-Delphi Survey, intervention components, stuttering